SIMULASI ANTRIAN UNTUK APPOINTMENT SCHEDULING PADA SISTEM PELAYANANKESEHATAN (STUDI KASUS POLIKLINIK PENYAKIT DALAM) - Diyah Pramita Sari; Anna Maria Sri Asih (Jurnal Teknosains, 2015)
Hospital as a health institution must be able to give good services for its stakeholders, especially patients. However, patients often have to wait for quite a long time in queues before service. A study case in an internal medicine polyclinic in a large scale hospital in Yogyakartashowed that for around 60 patients in a day, they have to stay in queues for more than one hour averagely. This observation occurred when appointment scheduling was used, i.e. patient must make an appointment for the service time. This research evaluated some scenarios that can reduce the waiting time in this system. Results showed that patient’s arrival was recommended to be schedulled every 15 minutes with adjustment on the number of operating server. This recommendation can reduce patient’s waiting time by 28-50% by taking into account the presence of the late doctors.